Knowledge, attitude and behaviour on salt intake and its association with hypertension in the Malaysian population: findings from MyCoSS (Malaysian Community Salt Survey) - Azli Baharudin; Rashidah Ambak; Fatimah Othman; Viola Michael; Siew Man Cheong; Nor Azian Mohd. Zaki; Nur Shahida Abdul Aziz; Syafinaz Mohd. Sallehuddin; Shubash Shander Ganapathy; Lalitha Palaniveloo; Feng J. He (BMC, 2021)
Abstract Background High blood pressure or hypertension has become one of the main health problems, worldwide. A number of studies have proven that an increased intake of salt was related to an increased prevalence of cardiovascular diseases. Of late, its relationship with high salt intake has received a lot of attention. Studies in Malaysia have shown both rising hypertension over time as well as high salt consumption. Actions to reduce salt intake are essential to reduce hypertension and its disease burden. As such, we carried out a study to determine associations between knowledge, attitude and behaviour towards salt intake and hypertension among the Malaysian population. Methods Data obtained from the Malaysian Community Salt Survey (MyCoSS) was used partially for this study. The survey used a cross-sectional two-stage sampling design to select a nationally representative sample of Malaysian adults aged 18 years and above living in non-institutional living quarters (LQ). Face-to-face interviews were done by trained research assistants (RA) to obtain information on sociodemography, medical report, as well as knowledge, attitude and behaviour of the respondents towards salt intake and blood pressure. Results Majority of the respondents have been diagnosed with hypertension (61.4%) as well as knowledge of the effects of high salt intake on blood pressure (58.8%). More than half of the respondents (53.3%) said they controlled their salt intake on a regular basis. Those who knew that a high salt diet could contribute to a serious health problem (OR=0.23) as well as those who controlled their salt intake (OR=0.44) were significantly less likely to have hypertension. Conclusion Awareness of the effects of sodium on human health, as well as the behaviour of controlling salt intake, is essential towards lowering the prevalence of hypertension among Malaysians.